Palestine, international law and Muslim unity - Eishan Jan, Mohammad Naqib (IIUM Press, 2010)
The Palestine issue is a heart breaking politico-legal issue that has remained unresolved for so long. The issue started immediately after the disintegration of the Ottoman Empire and following the occupation of Palestine by Great Britain. Britain disregarded the will of the majority of population, facilitated, directly or indirectly, Jewish settlements and supported foreign-led Zionist movement by making an unjust and illegal promise to them to create a state for Jews in Palestine which it eventually did and in doing so it further complicated the Palestine issue - an issue which the League of Nations was unable to solve due to its lack of commitment and its weak organizational structure. The issue has continued till today and is termed as "the most serious and prolonged unsolved political and human rights issue on the agenda of the United Nations (UN) since its inception".